Future precipitation and temperature changes over the Taro, Parma and Enza River Basins in Northern Italy - D’Oria, Marco; Cozzi, Chiara; Tanda, Maria Giovanna (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"This study analyzes the climate change effects on the future precipitation and temperature over the Taro, Parma and Enza River basins, in the Emilia Romagna region, northern Italy. An ensemble of 13 Regional Climate Models and two emission scenarios (RCP 4.5 and RCP 8.5) were adopted. The results are reported in terms of precipitation and mean temperature anomalies between a reference period (RP, 1986-2005) and three future periods: short-term (ST) 2016-2035, medium-term (MT) 2046-2065 and long-term (LT) 2081-2100. With reference to the rainfall data, irregular and slight variations are expected at any season and period; on a yearly scale, changes from -5% to +6% are estimated. On the other hand, a gradual warming of the study domain in the future periods is unequivocal. At annual scale, increments up to +0.75°C at ST,\r+1.5°C at MT and +2°C at LT are expected under the RCP 4.5, and higher, up to +4°C at LT with the RCP 8.5. In addition, the trend evolution of the climate variables was analyzed using a thirty-year moving time window up to the end of the century. From the results, it is evident that the pattern of the trend gradients follows the pattern of the scenario radiative forcing."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">This study analyzes the climate change effects on the future precipitation and temperature over the Taro, Parma and Enza River basins, in the Emilia Romagna region, northern Italy. An ensemble of 13 Regional Climate Models and two emission scenarios (RCP 4.5 and RCP 8.5) were adopted. The results are reported in terms of precipitation and mean temperature anomalies between a reference period (RP, 1986-2005) and three future periods: short-term (ST) 2016-2035, medium-term (MT) 2046-2065 and long-term (LT) 2081-2100. With reference to the rainfall data, irregular and slight variations are expected at any season and period; on a yearly scale, changes from -5% to +6% are estimated. On the other hand, a gradual warming of the study domain in the future periods is unequivocal. At annual scale, increments up to +0.75°C at ST, +1.5°C at MT and +2°C at LT are expected under the RCP 4.5, and higher, up to +4°C at LT with the RCP 8.5. In addition, the trend evolution of the climate variables was analyzed using a thirty-year moving time window up to the end of the century. From the results, it is evident that the pattern of the trend gradients follows the pattern of the scenario radiative forcing.